Measuring labour market flexibility in the OECD countries - Jaakko Kiander; Matti Virén (The Research Institute of the Finnish Economy (ETLA), 2000)
This paper investigates the adjustment of employment to population shocks in 22 OECD countries over the period 1960–1997. Most of the countries have experienced significant population shocks during that period – due to migration and other reasons. We estimate the speed of adjustment parameter which is used as a measure of the functioning of the labour market. If the OECD countries are compared using this measure, it turns out that the Anglo Saxon countries clearly outperform the other (European) countries in terms of labour market adjustment. In the case of the Nordic countries, the results presented are the most extreme. In practically all OECD countries, the functioning of the labour market seems to have deteriorated over time. These observations seem to be helpful in explaining for the behaviour of unemployment rates in the OECD area. – employment ; population shocks ; ageing ; migration
Keywords: J21; E24; 330; Bevölkerungsentwicklung; Beschäftigungseffekt; Messung; OECD-Staaten